Clinical predictors of benefit from fulvestrant in advanced breast cancer: A Meta-analysis of randomized controlled trials. (April 2016) - Graham, Jeffrey; Pitz, Marshall; Gordon, Vallerie; Grenier, Debjani; Amir, Eitan; Niraula, Saroj
Abstract: Background: Data on the comparative efficacy of fulvestrant and other endocrine treatments are inconsistent. Clinical markers predictive of greater benefit from fulvestrant compared to the alternate endocrine agents have not been identified. Methods: We searched the literature from inception to May 2015, using MEDLINE, EMBASE, and major conference proceedings. We included randomized controlled trials (RCTs) that compared fulvestrant containing arm to either tamoxifen or an aromatase inhibitors (AI) and presented results for subgroup analyses as Hazard Ratios (HR) for Time to Progression (TTP) or Progression Free Survival (PFS). Subgroup analyses reported in at least two RCTs were included. Data were then weighted using generic inverse variance approach and pooled in meta-analysis using RevMan 5.3 software. Difference between sub-groups was tested with chi 2 statistics. Results: Analysis included 4 RCTs comparing fulvestrant-based therapy to AI alone and comprising 2382 patients (1190 on fulvestrant and 1192 on control arms). TTP/PFS was the primary endpoint in all included studies. Four sub-groups fulfilled our criteria. Fulvestrant was associated with greater benefit in patients with visceral metastasis (HR 0.85 vs 1.02 for no visceral disease, p for difference = 0.05) and in those patients with a time to recurrence >5 years (HR 0.80 vs 1.09 for recurrence ⩽5 years, p for difference = 0.02). There was no apparent difference in benefit based on age >65 years (HR 0.86 vs 0.96, p for difference = 0.32) or HER2/neu status (HR 0.36 vs 0.92, p for difference = 0.09). Conclusion: Patients with advanced breast cancer with visceral involvement and longer time from diagnosis to recurrence had significantly better TTP/PFS with the use of fulvestrant. These results may have implications for selection of patients in the design of future clinical trials and to inform treatment decisions in clinical practice.